Visualisasi Data Penjualan Pada Online Shop Shillo Store Dengan Teknik Business Inteligence - Pendawa, Pancha Dimas (UNIVERSITAS KALBIS, 2023)
Shillo store is a women's clothing store based on an online shop where the products she sells are marketed on e-commerce Shoppe, this online shop has a problem where it is difficult to evaluate sales every month because the sales data produced is in excel format which is difficult to get the desired information because it is difficult to read it because there is so much data, as a result, when you get an order, the stock is not available. From this problem, it is proposed to use data visualization through a dashboard with a business intelligence roadmap technique. The output of this research is a visualization dashboard which helps the Shillo store to get the desired information in the monthly sales evaluation. And the tools used in this research are Tableau with the help of several charts and diagrams on Tableau.